Skills Training and Employment Outcomes in Rural Bihar - Bhaskar Chakravorty; Arjun S. Bedi (Institute of Labor Economics (IZA), 2017)
In a number of countries, youth unemployment is a pressing economic and political concern. In India, 54 percent of the country's population of 1.21 billion is below the age of 25 and faces a high rate of (disguised) unemployment. To augment youth employment, the Government of India has launched a number of skills training programs. This paper deals with participation in and the impact of one of these programs (DDUJKY) located in rural Bihar, one of India's poorest states. The analysis is based on data collected in mid-2016 and compares training participants with non-participants who applied for the scheme but eventually did not attend. We find that the training program squarely reaches the intended target group - rural poor youth. Initially, the program leads to a 29 percentage point increase in the employment rate of the trained graduates. However, two to six months after the training, the employment effect of the program drops to zero. A third of the placed graduates leave their jobs due to caste-based discrimination and another third leave due to a mismatch between the salaries offered and their living costs. The upshot is that while the training program enhances job market prospects, other labor market factors undo the positive effects.
Keywords: J60; J68; 330; India; Bihar; skills training; youth unemployment